Comparación de los desafíos del proceso de extracción en aceites esenciales en plantas oleaginosas - López Sornoza, Silvia Karina (2024)
The extraction of essential oils from oleaginous plants presents various challenges that vary depending on the extraction method chosen, the type of plant and the target compounds. These challenges include selecting the most suitable extraction method, optimizing process efficiency, minimizing the degradation of valuable compounds during extraction and storage, and managing the environmental impact associated with extraction. Optimizing process efficiency involves adjusting factors such as temperature, time, and feedstock-to-solvent ratio to maximize oil yield and quality, while preserving heat- and oxidation-sensitive compounds. Technological advances offer new extraction techniques, such as supercritical fluid extraction, that can offer better results in terms of throughput and selectivity, although often at greater cost and operational complexity. Finally, the environmental impact of essential oil extraction is a growing concern. This includes the consumption of resources, the generation of waste and the use of potentially harmful solvents.